Nanofibrous collagen nerve conduits for spinal cord repair - Houle, John D. (2013)
Nerve regeneration in an injured spinal cord is often restricted, contributing to the devastating outcome of neurologic impairment below the site of injury. Although implantation of tissue-engineered scaffolds has evolved as a potential treatment method, the outcomes remain sub-optimal. One possible reason may be the lack of topographical signals from these constructs to provide contact guidance to invading cells or regrowing axons. Nanofibers mimic the natural extracellular matrix architecturally and may therefore promote physiologically relevant cellular phenotypes. In this study, the potential application of electrospun collagen nanofibers (diameter=208.2±90.4 nm) for spinal cord injury (SCI) treatment was evaluated in vitro and in vivo. Primary rat astrocytes and dorsal root ganglias (DRGs) were seeded on collagen-coated glass cover slips (two-dimensional [2D] substrate controls), and randomly oriented or aligned collagen fibers to evaluate scaffold topographical effects on astrocyte behavior and neurite outgrowth, respectively. When cultured on collagen nanofibers, astrocyte proliferation and expression of glial fibrillary acidic protein (GFAP) were suppressed as compared to cells on 2D controls at days 3 (p<0.05) and 7 (p<0.01). Aligned fibers resulted in elongated astrocytes (elongation factor >4, p<0.01) and directed the orientation of neurite outgrowth from DRGs along fiber axes. In the contrast, neurites emanated radially on randomly oriented collagen fibers. By forming collagen scaffolds into spiral tubular structures, we demonstrated the feasibility of using electrospun nanofibers for the treatment of acute SCI using a rat hemi-section model. At days 10 and 30 postimplantation, extensive cellular penetration into the constructs was observed regardless of fiber orientation. However, scaffolds with aligned fibers appeared more structurally intact at day 30. ED1 immunofluorescent staining revealed macrophage invasion by day 10, which decreased significantly by day 30. Neural fiber sprouting as evaluated by neurofilament staining was observed as early as day 10. In addition, GFAP immunostained astrocytes were found only at the boundary of the lesion site, and no astrocyte accumulation was observed in the implantation area at any time point. These findings indicate the feasibility of fabricating 3D spiral constructs using electrospun collagen fibers and demonstrated the potential of these scaffolds for SCI repair.